Management of Hepatitis B Virus in Allogeneic Hematopoietic Stem Cell Transplantation - Wu, Yibo; Huang, He; Luo, Yi (Frontiers in Immunology, 2021)
The high morbidity of HBV reactivation following allogeneic hematopoietic stem cell transplantation (allo-HSCT) is partially due to the intense immunologic potency of complex therapeutic regimens, the use of antithymocyte globulin and calcineurin inhibitors to prevent graft versus-host disease (GVHD), prolonged immune reconstitution, and hematological malignancies infected with hepatitis B virus (HBV). Immunosuppression results in the reactivation of HBV replication from covalently closed circular DNA (cccDNA) residing in hepatocytes. However, the role of viral mutations during HBV reactivation needs to be validated. All individuals scheduled to receive allo-HSCT or wish to donate stem cells should be screened for hepatitis B surface antigen (HBsAg), antibodies to hepatitis B core (anti-HBc), and HBV-DNA. HBsAg-positive recipients of allo-HSCT have a high risk of HBV reactivation; thus, they should receive prophylactic antiviral therapy. The high barrier to resistance nucleos(t)-ide analogs (NAs) seems to be superior to the low barrier agents. Resolved-HBV recipients have a lower risk of HBV reactivation than HBsAg-positive recipients. Although prophylactic antiviral therapy remains controversial, regular monitoring of alanine transaminase (ALT) and HBV-DNA combined with preemptive antiviral treatment may be an optimized strategy. However, optimal antiviral therapy duration and time intervals for monitoring remain to be established. Accepting stem cells from HBsAg-positive donors is associated with a risk of developing HBV-related hepatitis. The overall intervention strategy, including donors and recipients, may decrease the risk of HBV-related hepatitis following HSCT from HBsAg positive stem cells. In this review, we summarize the issues of HBV in allo-HSCT, including HBV reactivation mechanism, HBsAg-positive recipients, HBV-resolved infection recipients, and donor-related factors, and discuss their significance.